1995
DOI: 10.1161/01.atv.15.8.1121
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor Pathway Inhibitor Activity Associated With LDL Is Inactivated by Cell- and Copper-Mediated Oxidation

Abstract: Human plasma contains a multivalent, Kunitz-type proteinase inhibitor termed tissue factor pathway inhibitor (TFPI), which is a specific inhibitor of the action of the factor VII(a)-tissue factor complex in coagulation. A major fraction of plasma TFPI is transported in association with LDL. Because LDL may undergo oxidation in the arterial wall during atherogenesis, we examined the effect of copper- and cell-mediated oxidative modification on TFPI activity associated with LDL. Oxidation mediated by copper ions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 61 publications
1
22
1
Order By: Relevance
“…Myeloperoxidase can exert prothrombotic activity via the generation of oxidant reactive species as it catalyzes lipid peroxidation in vivo, 36 thus leading to tissue factor activation 37 and tissue factor pathway inhibitor inactivation. 38 Myeloperoxidase reacts with hydrogen peroxide to form an enzyme substrate complex with strong oxidant activity and can bind firmly to negatively charged glycosaminoglycans and proteoglycans in the extracellular matrix. 39 In a previous postmortem study of patients dying suddenly of acute MI, Sugiyama et al 31 identified a novel subset of macrophages containing myeloperoxidase, infiltrating the subendothelium at sites of coronary plaque erosion or rupture, with few neutrophils in the same coronary lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Myeloperoxidase can exert prothrombotic activity via the generation of oxidant reactive species as it catalyzes lipid peroxidation in vivo, 36 thus leading to tissue factor activation 37 and tissue factor pathway inhibitor inactivation. 38 Myeloperoxidase reacts with hydrogen peroxide to form an enzyme substrate complex with strong oxidant activity and can bind firmly to negatively charged glycosaminoglycans and proteoglycans in the extracellular matrix. 39 In a previous postmortem study of patients dying suddenly of acute MI, Sugiyama et al 31 identified a novel subset of macrophages containing myeloperoxidase, infiltrating the subendothelium at sites of coronary plaque erosion or rupture, with few neutrophils in the same coronary lesions.…”
Section: Discussionmentioning
confidence: 99%
“…TFPI is a protease inhibitor that regulates TF-mediated coagulation by binding factor Xa and inactivating TF VII 37) . Most of TFPI activity in plasma is associated with lipoproteins where 40-80% of its activity is transported by apoB-containing particles, largely by LDL; however, cell-and copper-mediated oxidation, even when resulting in a low-oxidized product such as minimally modified LDL, significantly inactivated TFPI activity and neutralized its inhibitory influence on TF-PCA 38) . In addition, if TFPI-inhibited TF-PCA was truly the mechanism underlying the effect of higher-concentration oxLDL, then LPS-stimulated TF-PCA could not have been attenuated to the extent observed, and TF protein expression evaluated by Western blotting would not have shown the pattern demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…21 The purpose of this part of the study was to investigate the effects of mildly oxidized LDL on different forms of TFPI. Aliquots of LDL-r, or lipids alone, were incubated with recombinant TFPI, plasma TFPI, and Hep G-2 TFPI for 30 minutes before mild oxidation by exposure to air as described in Methods.…”
Section: Effect Of Oxidation On Tfpi-bound Ldl-rmentioning
confidence: 99%
“…20 It has also been shown that the inhibitory potential of TFPI may be compromised by lipoprotein oxidation. 21 The first 2 Kunitz domains within TFPI responsible for inhibiting clotting factors VIIa and Xa contain lysine and arginine residues at the inhibition sites. 22 The third Kunitz also contains a lysine residue at this site.…”
mentioning
confidence: 99%